Democratic Accountability and the Relative Obstacles to Foreign Investment - Fergal McCann; Michael Dorsch; Eoin McGuirk (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This paper considers the relationship between democratic accountability in de- veloping countries and the policies they use to attract foreign direct investment (FDI). We isolate two policy areas that governments of developing countries use to attract FDI: the tax burden on firms and the regulatory standards within which they operate. Countries that maintain high business taxes can only attract FDI by offering a less regulated business environment, which may have associated po- litical costs. The extent to which democratic accountability constrains leaders in their tax/regulatory policy choices is our main line of analysis. The novelty of the paper is that it endogenously determines policy choices within a political economy framework that recognizes the trade-offs between attracting FDI and maintaining political control. Examination of firm-level survey data from foreign firms operating in eastern Europe and central Asian economies confirms our model's main conclusion: regulation is seen to be a relatively larger obstacle to doing business in countries with greater democratic accountability.
Keywords: 330